Theory of social and economic organization - Weber, Max. (Glencoe, 1947)
Though an increasing number of scholars in the English-speaking world have in recent years come to know Max Weber's work in the original German editions, the part of it which has heretofore been available in English translation has formed a wholly inadequate basis on which to understand the general character of his contributions to social science. The Protestant Ethic and the Spirit of Capitalism is probably still his best-known work. This is an empirical historical essay which, in spite of its crucial significance to its author's work as a whole, is only a fragment even of his work on historical materials, and gives only an exceedingly partial idea of the analytical scheme upon which, to a very large extent, the interpretation of its significance depends. The General Economic History is far broader in scope but a mere sketch in development. It was put together from students' notes of the last series of lectures Weber gave and cannot be considered an adequate statement of the results of his researches in economic or institutional history, to say nothing of sociological theory and the methodology of social science.
Keywords: Sociology